Prevalence of Nutritional Status and Treatment Outcomes among Children with Acute Lymphoblastic Leukemia (ALL) After Induction of Chemotherapy Phase IA - Tiwari, Niva; Sharma, Krishna Sagar; Adhikari, Sudhir (Journal of College of Medical Sciences-Nepal, 2021)
Background Acute Lymphoblastic Leukemia (ALL) survival rates in high-income countries is more than 80% but less than 30% in low and middle-income countries (LMICs). A myriad of factors including the presence of malnutrition is said to contribute to it. However, controversy about the effect of weight, BMI and nutritional status on survival and remission outcomes exist hence this study was conceptualized. Methods A retrospective cross sectional study was conducted in the department of Pediatric Oncology Unit, B.P. Koirala Memorial Cancer Hospital, Chitwan, Nepal. Patients with ALL diagnosis falling in normal weight or underweight category were included based under Z-score. Data was analyzed using descriptive and inferential Statistical tools usign SPSS. Study was conducted after taking ethical approval from IRC of BPKMCH. Results Among eighty two participants, majority of the children were less than 5 years age group, 91.5% were underweight (with 95% CI as 80.84% to 96.71%). There were four deaths and one refused treatment, four patients relapse and 59 had remission in underweight group. The statistically significant variable associated with nutritional staus as age. Conclusions The prevalence of underweight among ALL patients was high and in remission group they were relatively better nourished than other.